Moderasi Beragama: Pandangan Lukman Hakim Saifuddin terhadap Kehidupan Beragama di Indonesia - Mochammad Nginwanun Likullil Mahamid (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2023)
This article was written to analyze religious moderation understanding, which had recently become an interesting discussion among the public. It was even predicted that the spirit of the idea could give a feeling of peace to every believer in religion. On the other hand, its presence is seen as weakening religious belief. In addition, other accusations seem to support certain agendas degrading religious values, especially Islam, such as liberalism and secularism. Referring to this case, Lukman Hakim Saifuddin as a scholar and intellectual who received an honorary degree in the field of religious moderation, also expressed his thoughts through a book entitled “Moderasi Beragama: Tanggapan atas Masalah, Kesalahpahaman, Tuduhan, dan Tantangan yang Dihadapinya,” published in 2022, which is the focus writing of this article. By using the descriptive-analytic method, a number of findings were attempted in this article, including an overview of the book on moderation understanding, which significantly influenced the life of religious communities in Indonesia. Then, the comparison of previous studies that were relevant to this idea, as well as to answer negative accusations by some people who did not fully understand the urgency of the existence of religious moderation, as well as the evaluation of books, both in terms of academic strengths and weaknesses.